UTOPIAN MOTIFS AND NATIONAL IDENTITY IN AMERICAN LITERARY TRADITION - Rakhmanov K. S.; Rustamova M. Y. (American Journals Publishing, 2025)
This article analyzes what should be considered when developing a unified veterinary information system in Uzbekistan, as well as veterinary information systems developed in foreign countries and their functional capabilities.
Keywords: Veterinary unified information system, digital transformation, digital integration, foreign experience, database, border veterinary post, information exchange.